STRATEGI MENINGKATKAN MARKETING SKILL SECARA CEPAT DAN EFEKTIF - Mulia Syahputri; Zuhrinal M. Nawawi (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze effective strategies to rapidly enhance marketing skills among individuals and target groups. In the dynamic digital era, mastering marketing skills is a key factor in improving competitiveness and business success. The research employs a qualitative approach using library research and document analysis, reviewing literature, previous studies, and related documents on marketing skill development. The findings reveal that effective marketing skill enhancement strategies integrate experiential learning, digital literacy, adaptive learning technology, social networks, and optimal resource management. Active and self-directed learning approaches accelerate skill acquisition, while digital literacy and utilization of digital marketing tools are essential prerequisites. Social networks and practitioner communities strengthen collaboration and innovation, whereas adaptive technology personalizes learning processes for greater efficiency. The study also identifies barriers such as limited technology access and resistance to new learning methods, which can be overcome through flexible program design and blended learning. In conclusion, this comprehensive and integrative strategy not only improves individual competencies but also significantly impacts business growth and competitiveness in the digital era. These findings are expected to serve as a reference for educational institutions, business actors, and training providers in developing innovative and sustainable marketing skill enhancement programs.